DEVELOPMENT OF CAS9 PROTEIN EXPRESSION SYSTEM THROUGH CO-TRANSLATION WITH DOWNSTREAM CHAPERONES IN BICISTRONIC SYSTEM - Josefanny
Clustered Regularly Interspaced Short Palindromic Repeats associated 9 (CRISPR-Cas9) is an effective and efficient genetic modification technique. This system is composed of Single-Guide RNA (sgRNA) that can be designed to target specific DNA sequences and Cas9 protein with endonuclease activity. Currently, the CRISPR-Cas9 system has developed applications in the field of genetic engineering. Cas9 protein and sgRNA delivery systems in the form of ribonucleoproteins (RNPs) are more desirable because they have lower immunogenicity and offtarget potential. However, Cas9 protein has a relatively large size (158 kDa) triggering the tendency of non-functional Cas9 protein aggregation in recombinant protein production with E. coli. One approach to produce soluble and functional proteins is using Chaperone-Substrate Co- Localized Expression (CLEX). This method will be adapted to increase the percentage of functional recombinant Cas9 protein. An overlapping area between the DNA sequence encoding the Cas9 protein and the chaperone DnaJ was designed. This system was conceived with the aim of increasing the folding efficiency of the Cas9 protein through increasing the probability of interaction between the Cas9 protein and the DnaJ chaperone. The two coding regions were integrated in the pRSFDuet-1 expression vector with the expression host being E. coli BL21(DE3). The test was conducted by analyzing the relative percentage of soluble Cas9 produced with and without the CLEX system based on SDS-PAGE results. The results showed that the percentage of soluble Cas9 protein produced through the CLEX system was not higher than the control production (without CLEX). This is thought to be due to the large size of the target protein and the increased metabolic load with the addition of the CLEX system. Tests showed that temperature (18, 25, 30 and 37 oC) and expression duration (4, 6 and 16 hours) were significant factors that determined the percentage solubility of Cas9 target protein. There was a decrease in the relative percentage of soluble Cas9 in the system with and without CLEX as the temperature and duration of expression increased. However, it was found that the CLEX system obtained a higher percentage of soluble Cas9 than the system without CLEX at a temperature of 30 oC and an expression duration of 16 hours. Therefore, this system can be applied to express proteins without the use of a cold room incubator for a long and continuous duration. The linear regression results also showed that the CLEX system slowed down the formation of the insoluble fraction as the temperature and duration of expression increased. Endonuclease activity testing on Cas9 proteins produced with and without the CLEX system showed that the endonuclease activity in vitro was not different.